2011
DOI: 10.1371/journal.pone.0017553
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D Receptor Silencing on the Expression of LVSCC-A1C and LVSCC-A1D and the Release of NGF in Cortical Neurons

Abstract: BackgroundRecent studies have suggested that vitamin D can act on cells in the nervous system. Associations between polymorphisms in the vitamin D receptor (VDR), age- dependent cognitive decline, and insufficient serum 25 hydroxyvitamin D3 levels in Alzheimer's patients and elderly people with cognitive decline have been reported. We have previously shown that amyloid β (Aβ) treatment eliminates VDR protein in cortical neurons. These results suggest a potential role for vitamin D and vitamin D-mediated mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 41 publications
4
111
0
2
Order By: Relevance
“…Our recent in vitro experiments also provided some explanation for the biological function of the vitamin D-VDR pathway in AD and neurodegeneration Gezen-Ak et al 2011). We showed that amyloid beta suppressed the expression of VDR in cortical neurons and suggested that vitamin D supplementation may prevent amyloid induced cytotoxicity ).…”
Section: Tohoku University Medical Pressmentioning
confidence: 79%
“…Our recent in vitro experiments also provided some explanation for the biological function of the vitamin D-VDR pathway in AD and neurodegeneration Gezen-Ak et al 2011). We showed that amyloid beta suppressed the expression of VDR in cortical neurons and suggested that vitamin D supplementation may prevent amyloid induced cytotoxicity ).…”
Section: Tohoku University Medical Pressmentioning
confidence: 79%
“…The knock-out model of VDR-/-has an accelerated aging process in all the organs, and in the brain [17][18], with a significant in-brain decrease of NGF [19] and of other neurotransmitters, such as acetylcholine [20][21][22][23][24]. Congenital deficiency of vitamin D significantly reduces the activity of glutamic acid decarboxylase (GAD) 65/67 (key enzymes in GABAergic inter-neurons) and the levels of glutamate and glutamine in brain tissue [25].…”
Section: Methabolism and Biological Actions Of Vitamin Dmentioning
confidence: 99%
“…The variables required descriptive nominal and ordinal possible answer choices in order to facilitate the response method of individuals, due to the study relying on personal response and opinion rather than numerical data or accurate serum analyses. The variables represented and mentioned in the objectives above are, respectively: sun exposure (or not) during a specific timing (between 10 am and 3 pm), type of Sun protection factor (SPF) (8,15, more than 15, none), frequency of Sun protection factor application (frequently, usually/sometimes, rarely), frequency of practicing sunbathing (frequently, sometimes/during holidays, rarely), type of clothes and coverage (covering the whole body with religious "Hijab", not covering the whole body with arms, face, or legs uncovered), daily work/educational environment (indoors or a mix of outdoors and indoors according to the type of daily transportation used), nature of physical activity usually practiced (active lifestyle, usually practicing outdoor activities, sedentary lifestyle), types of food containing natural and fortified Vitamin D and choice of more than one type frequently consumed (cod liver oil, salmon, tuna, sardines, liver/beef, orange juice, milk, yoghurt, and readymade cereals), and finally current weight range (underweight, normal weight, overweight, obese).…”
Section: Resultsmentioning
confidence: 99%
“…It's important to have "sun exposure between the hours of 10:00 and 15:00 in the spring, summer, and autumn, because this is the only time when enough UVB photons reach the earth's surface to produce vitamin D 3 in the skin" 13 The amount of sunbathing, in accordance with skin pigmentation, mainly affects the degree of being exposed to the sun where one practicing sunbathing will often result in achieving the recommended intake of Vitamin D as opposed to not sunbathing, however it is notable that lighter pigmented people absorb more than dark pigmented due to the latter requiring a larger amount of exposure to reach levels of the former 14 Furthermore, sunscreens with an Sun protection factor factor of 8 reduce the skin's synthesis of vitamin D 3 by >95% whereas an Sun protection factor factor of 15 reduces synthesis by >98%. 15 The frequency of sunscreen application is also of great significance in relation to causing Vitamin D deficiency, especially due to the possibility of women using it much more than men.…”
Section: Discusionmentioning
confidence: 99%